Growth Performance and Feeding Efficiency of Goldfish (Carassius auratus) and Red Cap Oranda Fish (Carassius auratus auratus) by Using Different Locally Prepared Feed Mixed with Different Plant Extracts at Paklihawa, Nepal - Gurung, S.; Bohara, K.; Adhikari, R.; Bista, A.; Singh, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
A research was done at Aquaculture department laboratory of Institute of Agriculture and Animal Science Paklihawa Campus, Rupandehi from 28 February 2017 to 28 April 2017 using two ornamental fishes; Goldfish (Carassius auratus) and Red cap oranda (Carassius auratus auratus) . Twelve rectangular glass aquarium of size of 12” × 24” × 12” were used for the purpose to assess the growth performance and feeding efficiency. Four treatments selected for this purpose were local feed containing rice bran and mustard oil cake (MOC) in T1 (Control), Local Feed with 5% Cassava leaves powder in T2, Local Feed with 5% Sweet Potato leaves powder in T3 and Local Feed with 5% Colocasia leaves powder 5% T4 during the experimental period. The initial weight of red cap was significantly lower in T3 as compared to T1 but was at par with T2 and T4. Furthermore, the final weight was not significantly different among the treatments. In case of goldfish, the initial weight at T4 was significantly lower than T2 but was at par among other treatments. The final weight was significantly higher in T2 as compared to T4 and T3 was at par with T1. Feed conversion ratio (FCR) was observed higher in case of T2 (6.981±3.14) and lower in case of T3 (3.325±0.48). However, no significant difference was noticed among the treatments. Specific growth rate (SGR) was observed higher in T3 (0.0370±0.088) as compared to other treatments. However, in this case also, no significant difference was observed. Survivability percentage for red cap fish was observed higher in T3 (100±0.00) and least inT2 (50.000±40.82), whereas, survivability was 100% for goldfish in all the treatments. The average survivability was highest (100%) in T3 for both kinds of fishes and minimum in T2 (75±20.41). Also, the mean pH observed at T1, T2, T3 and T4 was 9.165, 9.222, 9.196 and 9.172 respectively. Similarly, daily mean dissolved oxygen recorded at T1, T2, T3 and T4 was 6.23 mg/l, 6.16 mg/l, 6.267mg/l and 6.147 mg/l respectively. Moreover, the mean average temperature recorded in these four treatments; T1, T2, T3 and T4 were 23.342°>C, 23.272°C, 23.342°C and 23.339°C respectively.